Metal-loaded SBA molecular sieve as well as preparation method and application thereof
By using metal-supported SBA molecular sieve in the CO methanation catalyst and forming a silicon dioxide film on its outer surface, the problem of metal components loss in the catalyst is solved, the life of the catalyst is extended and the catalytic effect is improved.
Patent Information
- Application Number
- CN202310944739.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-28
AI Technical Summary
The existing iron-cobalt nickel-based CO methanation catalysts are prone to loss of metal components during the reaction, resulting in a shortening of the catalyst service life and a reduction in the catalytic effect.
A metal-supported SBA molecular sieve is adopted to prepare a metal source by adding a metal source during the molecular sieve forming stage and forming a silicon dioxide film on the outer surface of the molecular sieve to protect the metal active site and prevent metal loss.
It effectively extends the service life and activity of the catalyst, improves CO conversion and methane yield, and avoids the catalyst deactivation caused by agglomeration of metal particles at high temperatures.
Smart Images

Figure CN119425763A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieve preparation, and more specifically to a metal-loaded SBA molecular sieve and a preparation method and application thereof. Background Art
[0002] The main reaction of CO methanation is a highly exothermic reaction. Every 1% increase in conversion will increase the bed temperature of the methanation reactor by 74°C. At the same time, many side reactions also occur, resulting in complex reactions including CO2 and C n (n≥2). Based on the strong exothermic characteristics of the CO hydrogenation reaction, iron-cobalt-nickel-based catalysts have attracted much attention due to their low price and high catalytic activity. Therefore, many studies are devoted to the research of iron-cobalt-nickel-based CO methanation catalysts. However, there are also many problems with iron-cobalt-nickel-based CO methanation catalysts. In the reactor, since a large amount of heat is released by the conversion of CO, it is easy to cause local overheating of the catalyst. The iron-cobalt-nickel metal particles are easy to agglomerate to form large particles at a higher temperature, resulting in catalyst deactivation and shortening the service life of the catalyst. In addition, the existing iron-cobalt-nickel-based CO methanation catalysts are basically supported catalysts prepared by post-treatment and other means. The metal is distributed on the surface of the molecular sieve. Therefore, it is very easy to cause the loss of metal components during the reaction, resulting in a reduction in the service life of the catalyst and a reduction in the catalytic effect. Summary of the invention
[0004] The purpose of the present invention is to provide a metal-loaded SBA molecular sieve and a preparation method thereof, so as to solve the technical problem in the prior art that the metal components in the catalyst are dispersed on the surface of the molecular sieve, which easily causes the loss of the metal components during the reaction, thereby shortening the service life of the catalyst and reducing the catalytic effect.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing a metal-loaded SBA molecular sieve, comprising:
[0007] S1. Mixing SBA molecular sieve powder, a metal source, a first silicon source and an alkaline solution to obtain a mixture, and forming and drying the mixture to obtain molecular sieve A;
[0008] S2. The organic template R, water, a second silicon source and an acid are mixed to obtain a solution B;
[0009] S3. Add solution B to molecular sieve A, perform hydrothermal crystallization, filter, wash, dry and calcine to obtain the metal-loaded SBA molecular sieve.
[0010] In the preparation method of the metal-loaded SBA molecular sieve provided by the present invention, the first silicon source is hydrolyzed under the action of an alkaline solution to generate a viscous silica mesh, and the viscous silica mesh bonds the molecular sieve particles to each other. After extrusion molding, the viscous silica mesh transforms a silicon dioxide film under the conditions of high temperature roasting, covering the silicon hydroxyl structure on the outer surface of the molecular sieve, and due to the silicon dioxide film and the skeleton structure silicon oxygen structure type of the molecular sieve itself, the outer surface of the molecular sieve will not be covered and blocked, and in practical applications, the reactant will enter the outer surface of the molecular sieve from the silicon dioxide film in the form of diffusion. However, due to the metal distribution on the outer surface of the molecular sieve, the silicon dioxide film formed will have a gap at the position of the metal, and hydrothermal crystallization is carried out by adding a mixed solution of an organic template agent R, water, a second silicon source and an acid, and the position of the gap is crystallized and grown, forming a complete silicon dioxide film on the outer surface of the molecular sieve. These silicon dioxide films can improve the mechanical strength of the molecular sieve and provide a protective film for the molecular sieve structure itself. Since this protective film is similar to the silicon dioxide structure of the molecular sieve skeleton structure, it will not affect the activity and diffusion performance of the molecular sieve itself, and it can also make the metal active sites difficult to lose during the reaction process, effectively extending the life and activity of the catalyst. In addition, the silicon dioxide film formed on the outer surface of the molecular sieve can also effectively avoid the problem of metal particles agglomerating at high temperatures and causing catalyst deactivation.
[0011] According to some embodiments of the present invention, the SBA molecular sieve raw powder includes SBA-15 molecular sieve raw powder or SBA-16 molecular sieve raw powder.
[0012] According to some embodiments of the present invention, the metal source includes at least one of an iron source, a cobalt source, and a nickel source.
[0013] According to some embodiments of the present invention, the iron source includes at least one of potassium ferrocyanide, potassium ferrocyanide, and ferric nitrate, preferably ferric nitrate.
[0014] According to some embodiments of the present invention, the cobalt source includes at least one of cobalt nitrate, cobalt oxide, and cobalt hydroxide, preferably cobalt oxide.
[0015] According to some embodiments of the present invention, the nickel source includes at least one of nickel nitrate, nickel oxide, and nickel hydroxide, preferably nickel oxide.
[0016] According to some embodiments of the present invention, the first silicon source includes at least one of tetraethyl orthosilicate (TEOS), silica sol, and water glass, preferably tetraethyl orthosilicate.
[0017] According to some embodiments of the invention, the base in the alkaline solution comprises NaOH.
[0018] According to some embodiments of the present invention, the amphiphilic nonionic triblock surfactant F127 (EO 106 PO 70 EO 106 )、F108(EO 132 PO 50 EO 132 )、hexamethylenetetramine (HMTA), P123 (EO 20 PO 70 EO 20 )、P104(EO 27 PO 61 EO 27 ) at least one of.
[0019] According to some embodiments of the present invention, when the SBA molecular sieve raw powder includes SBA-15 molecular sieve raw powder, R is selected from at least one of P123 and P104.
[0020] According to some embodiments of the present invention, when the SBA molecular sieve raw powder includes SBA-16 molecular sieve raw powder, R is selected from at least one of F127, F108, and HMTA.
[0021] According to some embodiments of the present invention, the second silicon source includes at least one of white carbon black, tetraethyl orthosilicate (TEOS), sodium silicate, and silica sol, preferably tetraethyl orthosilicate.
[0022] According to some embodiments of the present invention, the acid includes at least one of hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid.
[0023] According to some embodiments of the present invention, the mass ratio of the metal source to the SBA molecular sieve raw powder is 1 to 10:100.
[0024] According to some embodiments of the present invention, the mass ratio of the first silicon source to the SBA molecular sieve raw powder is 1:5-10.
[0025] According to some embodiments of the present invention, the alkali solution contains OH - The ratio of the molar amount of the base calculated as SiO2 to the molar amount of the first silicon source calculated as SiO2 is 0.5 to 4:1.
[0026] According to some embodiments of the present invention, the alkali solution contains OH - The ratio of the molar amount of the base calculated as SiO2 to the molar amount of the first silicon source calculated as SiO2 is 0.5 to 3.5:1.
[0027] According to some embodiments of the present invention, the molar ratio of the components in the solution B is SiO2:a H2O:b R:c H +, wherein the value of a is 80 to 200, preferably 100 to 160, the value of b is 0.005 to 0.030, preferably 0.010 to 0.025, and the value of c is 0.10 to 0.25, preferably 0.15 to 0.20.
[0028] According to some embodiments of the present invention, the mixture in step S1 is first dried, and then the dried mixture is mixed with water and molded.
[0029] According to some embodiments of the present invention, the mass of water mixed with the dried mixture is 10% to 30%, preferably 15% to 25% of the mass of the dried mixture.
[0030] According to some embodiments of the present invention, the drying temperature in step S1 is 100-140°C, preferably 110-130°C.
[0031] According to some embodiments of the present invention, the crystallization temperature in step S3 is 80 to 130° C., preferably 90 to 120° C.; the crystallization time is 24 to 90 hours, preferably 40 to 70 hours.
[0032] According to some embodiments of the present invention, the drying temperature in step S3 is 100-140°C, preferably 110-130°C.
[0033] According to some embodiments of the present invention, the calcination temperature in step S3 is 400-700° C., preferably 500-600° C.; and the calcination time is 5-8 hours.
[0034] In a second aspect, the present invention provides a metal-loaded SBA molecular sieve prepared by the preparation method described in the first aspect.
[0035] According to some embodiments of the present invention, the surface of the metal-loaded SBA molecular sieve comprises a silica shell layer.
[0036] According to some embodiments of the present invention, the particle size of the metal-loaded SBA molecular sieve is 80-120 nm.
[0037] In a third aspect, the present invention provides the use of the metal-loaded SBA molecular sieve described in the second aspect in a CO methanation reaction.
[0038] According to some embodiments of the present invention, the metal-supported SBA molecular sieve is subjected to a pre-reduction treatment before being used in the CO methanation reaction.
[0039] According to some embodiments of the present invention, the pre-reduction treatment includes: first heating to 400-500°C under N2 atmosphere with a nitrogen flow rate of 10-20mL / min; switching to H2 for pre-reduction for 2-4h with a hydrogen flow rate of 20-30mL / min; and then cooling down to 180-230°C under N2 atmosphere.
[0040] According to some embodiments of the present invention, the heating rate is 20-30°C / min.
[0041] According to some embodiments of the present invention, the reaction temperature is 180-230°C;
[0042] According to some embodiments of the present invention, the CO methanation reaction comprises a reaction of a reaction mixture under the action of the metal-loaded SBA molecular sieve, wherein the reaction mixture comprises H2, CO and N2.
[0043] According to some embodiments of the present invention, the volume ratio of H2, CO and N2 in the reaction mixture is 2 to 4:1:1.
[0044] The beneficial effects of the present invention are at least:
[0045] The preparation method of the metal-loaded SBA molecular sieve provided by the present invention is simple, a metal source is directly added in the molecular sieve forming stage, and the molecular sieve does not need to be impregnated with a metal solution, and the forming and metal impregnation processes are completed in one step; the prepared metal-loaded SBA molecular sieve is covered with a silicon dioxide film on the outside of the molecular sieve, which provides a protective film for the structure of the molecular sieve itself, so that the metal active sites are not easily lost during the reaction process, and the life and activity of the catalyst are effectively extended. The metal-loaded SBA molecular sieve is used in the CO methanation reaction, which can significantly improve the CO conversion rate and the methane yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a scanning electron microscope image of the catalyst prepared in Example 3.
[0047] Figure 2 This is the XPS graph of the iron atom of the catalyst prepared in Example 3. DETAILED DESCRIPTION
[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0049] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0050] Among them, XPS uses Thermo's ESCALAB 250spectrometer X-ray photoelectron spectrometer to measure the bonding of metal particles.
[0051] The scanning electron microscope used was Hitachi S-4700 scanning electron microscope.
[0052] Example 1
[0053] S1. Add 40g of SBA-16 molecular sieve powder, 0.8g of potassium ferrocyanide, 4g of tetraethyl orthosilicate (TEOS) and 0.3L of 0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 100°C. Then take 30g of the dried sample and put it into an extruder. Add 3g of deionized water and stir evenly to start molding. The molded molecular sieve is dried at 100°C and recorded as molecular sieve A.
[0054] S2. 1.6 g F127 and 34.5 g deionized water were added to the reactor in sequence, stirred evenly, and then 24.1 mL hydrochloric acid solution (0.1 mol / L) was added. Stirring was continued, and 5 g tetraethyl orthosilicate (TEOS) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 80H2O: 0.005R: 0.1H + .
[0055] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 90°C, and crystallize at a constant temperature for 40 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 100°C, and finally calcine it at 400°C for 8 hours to obtain the molecular sieve sample.
[0056] Example 2
[0057] S1. Add 40g SBA-16 molecular sieve powder, 1.6g potassium ferrocyanide, 6g silica sol (SW-25, silicon dioxide content is 25wt%) and 0.3L 0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 110°C. Then take 30g of the dried sample and put it into an extruder. Add 6g deionized water and stir evenly before starting to shape it. The formed molecular sieve is dried at 110°C and recorded as molecular sieve A.
[0058] S2. 4.4 g F108 and 54 g deionized water were added to the reactor in sequence, stirred evenly, and then 44.8 mL sulfuric acid (0.1 mol / L) was added, stirring was continued, and 2 g white carbon black (silicon dioxide content was 90 wt%) was added to obtain solution B. The molar ratio of each component in solution B was SiO2: 100H2O: 0.01R: 0.15H + .
[0059] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 100°C, and crystallize at a constant temperature for 50 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 110°C, and finally calcine it at 500°C for 6 hours to obtain the molecular sieve sample.
[0060] Example 3
[0061] S1. Add 40g of SBA-16 molecular sieve powder, 3.2g of ferric nitrate, 6g of tetraethyl orthosilicate (TEOS) and 0.15L of 0.1mol / L NaOH solution into a mortar and mix. After mixing evenly, dry and dry at 120°C. Then take 30g of the dried sample and put it into an extruder. Add 7.5g of deionized water and stir evenly before forming. The formed molecular sieve is dried at 120°C and recorded as molecular sieve A.
[0062] S2. 0.15 g HMTA and 82.5 g deionized water were added to the reactor in sequence, stirred evenly, and then 83 mL nitric acid solution (0.1 mol / L) was added. Stirring was continued, and 10 g silica sol (SW-25, with a silicon dioxide content of 25 wt%) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 110H2O: 0.025R: 0.2H + .
[0063] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 110°C, and crystallize at a constant temperature for 60 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 120°C, and finally calcine it at 550°C for 7 hours to obtain the molecular sieve sample.
[0064] SEM images of the samples are shown in Figure 1 The state of iron atoms in the molecular sieve is analyzed by XPS. Figure 2 .
[0065] Depend on Figure 1 and Figure 2 It can be seen that the metal in the sample is distributed on the outer surface of the molecular sieve in the form of oxides (the peak of XPS iron oxide is 458.5 eV). Figure 1 It can be clearly seen that the outer surface of the sample is a silicon dioxide film, and no metal oxides can be seen in the entire field of view, indicating that the metal oxides are distributed on the outer surface of the molecular sieve within the silicon dioxide film. Since the outer surface of the molecular sieve is protected by the silicon dioxide film, the metal on the outer surface of the molecular sieve is not easily lost during the reaction, thereby extending the service life of the catalyst.
[0066] Example 4
[0067] S1. Add 40g of SBA-15 molecular sieve powder, 3.2g of cobalt nitrate, 6g of tetraethyl orthosilicate (TEOS) and 0.3L of 0.1mol / L NaOH solution into a mortar and mix. After mixing evenly, dry and dry at 130°C. Then take 30g of the dried sample and put it into an extruder. Add 7.5g of deionized water and stir evenly before forming. The formed molecular sieve is dried at 130°C and recorded as molecular sieve A.
[0068] S2. 4.2 g P104 and 38.9 g deionized water were added to the reactor in sequence, stirred evenly, and then 60 mL hydrochloric acid solution (0.1 mol / L) was added. Stirring was continued, and 5 g tetraethyl orthosilicate (TEOS) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 90H2O: 0.03R: 0.25H + .
[0069] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 130°C, and crystallize at a constant temperature for 90 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 130°C, and finally calcine it at 400°C for 8 hours to obtain the molecular sieve sample.
[0070] Example 5
[0071] S1. Add 40g of SBA-15 molecular sieve powder, 3.2g of nickel nitrate, 8g of tetraethyl orthosilicate (TEOS) and 1.2L of 0.1mol / L NaOH solution into a mortar and mix. After mixing evenly, dry and dry at 120°C. Then take 30g of the dried sample and put it into an extruder. Add 7.5g of deionized water and stir evenly before forming. The formed molecular sieve is dried at 120°C and recorded as molecular sieve A.
[0072] S2. 4.2 g P104 and 38.9 g deionized water were added to the reactor in sequence, stirred evenly, and then 60 mL hydrochloric acid solution (0.1 mol / L) was added. Stirring was continued, and 5 g tetraethyl orthosilicate (TEOS) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 90H2O: 0.03R: 0.25H + .
[0073] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 130°C, and crystallize at a constant temperature for 90 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 120°C, and finally calcine it at 400°C for 8 hours to obtain the molecular sieve sample.
[0074] Comparative Example 1
[0075] 40g SBA-15 molecular sieve powder and 14.2g pseudo-boehmite (Al2O3 content is 70%) are added to a mixer and mixed. After mixing evenly, 25.8g dilute nitric acid (HNO3 content is 6.3wt%) is added for kneading, and then 15.5g deionized water is added for further kneading. The kneaded material is then put into an extruder for molding. The molded molecular sieve is dried at 130°C and then calcined at 400°C for 8h. The calcined molecular sieve is then mixed with 3.2g ferric nitrate for 4h, dried at 130°C and then calcined at 400°C for 8h to obtain a Fe / SBA-15 molecular sieve sample.
[0076] Comparative Example 2
[0077] The test process refers to Example 4, and the only difference from Example 4 is that the amount of 0.1 mol / L NaOH solution is changed from 0.3 L to 2.1 L.
[0078] Catalytic effect evaluation
[0079] The molecular sieve samples prepared in the examples and comparative examples were used for CO methanation reaction, and the specific process was as follows:
[0080] The CO methanation reaction was carried out in a fixed bed pressurized microreactor, and the catalyst was loaded in the middle of the reaction tube. 0.2 g of the catalyst was first heated to 500°C at a heating rate of 20°C / min in a 10 mL / min N2 atmosphere, then pre-reduced with 20 mL / min H2 for 2 h, cooled to 200°C in a N2 atmosphere, and then the gas was switched to a reaction mixed gas, in which V(H2):V(CO):V(N2) was 3:1:1. After 1 h, the product composition was analyzed online by gas chromatography. The test results are shown in Table 1.
[0081] Table 1 Experimental results of CO methanation reaction
[0082] CO conversion rate (%) Methane yield (%) Example 1 97.1 87.1 Example 2 97.5 87.7 Example 3 98.3 88.5 Example 4 99.8 90.4 Example 5 98.4 88.9 Comparative Example 1 62.7 19.8 Comparative Example 2 23.6 3.7
[0083] It can be seen from the above test results that the catalyst prepared by the preparation method provided by the present invention exhibits excellent catalytic performance in CO methanation reaction.
[0084] Comparative Example 1 uses a traditional molding method. Firstly, due to the addition of adhesive during the molding process, the catalyst prepared by the traditional method has relatively fewer active sites among catalysts of the same mass. Secondly, due to the lack of protection of the outer surface silica film, the metal on the surface of the molecular sieve is very easy to be lost during the reaction, which will cause the catalyst activity to decrease.
[0085] In Comparative Example 2, due to the addition of too much alkali, the framework of the molecular sieve itself will collapse while the silicon source is hydrolyzed to form a silicon dioxide film and a sticky network, so the catalytic activity is very low.
[0086] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a metal-loaded SBA molecular sieve, characterized in that: include: S1. Mixing SBA molecular sieve powder, a metal source, a first silicon source and an alkaline solution to obtain a mixture, and forming and drying the mixture to obtain molecular sieve A; S2. The organic template R, water, a second silicon source and an acid are mixed to obtain a solution B; S3. Add solution B to molecular sieve A, perform hydrothermal crystallization, filter, wash, dry and calcine to obtain the metal-loaded SBA molecular sieve.
2. The preparation method according to claim 1, characterized in that: The SBA molecular sieve raw powder includes SBA-15 molecular sieve raw powder or SBA-16 molecular sieve raw powder; And / or, the metal source includes at least one of an iron source, a cobalt source, and a nickel source; preferably, the iron source includes at least one of potassium ferrocyanide, potassium ferrocyanide, and ferric nitrate, preferably ferric nitrate; and / or the cobalt source includes at least one of cobalt nitrate, cobalt oxide, and cobalt hydroxide, preferably cobalt oxide; and / or the nickel source includes at least one of nickel nitrate, nickel oxide, and nickel hydroxide, preferably nickel oxide; and / or, the first silicon source comprises at least one of tetraethyl orthosilicate, silica sol, and water glass, preferably tetraethyl orthosilicate; And / or, the alkali in the alkali solution comprises NaOH.
3. The preparation method according to claim 1 or 2, characterized in that: The organic template R includes at least one of F127, F108, hexamethylenetetramine, P123, and P104; and / or, the second silicon source comprises at least one of white carbon black, tetraethyl orthosilicate, sodium silicate, and silica sol, preferably tetraethyl orthosilicate; And / or, the acid includes at least one of hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid.
4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the metal source to the SBA molecular sieve raw powder is 1 to 10:100; And / or, the mass ratio of the first silicon source to the SBA molecular sieve raw powder is 1:5-10; And / or, the alkaline solution contains OH - The ratio of the molar amount of the base calculated as SiO2 to the molar amount of the first silicon source calculated as SiO2 is 0.5 to 4:
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of each component in the solution B is SiO2:a H2O:b R:c H + , wherein the value of a is 80 to 200, preferably 100 to 160, the value of b is 0.005 to 0.030, preferably 0.010 to 0.025, and the value of c is 0.10 to 0.25, preferably 0.15 to 0.
20.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The mixture in step S1 is first dried, and then the dried mixture is mixed with water and then formed; Preferably, the mass of water mixed with the dried mixture is 10% to 30%, preferably 15% to 25% of the mass of the dried mixture.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The drying temperature in step S1 is 100-140°C, preferably 110-130°C; And / or, the crystallization temperature in step S3 is 80-130° C., preferably 90-120° C.; the crystallization time is 24-90 hours, preferably 40-70 hours; And / or, the drying temperature in step S3 is 100-140° C., preferably 110-130° C.; And / or, the calcination temperature in step S3 is 400-700° C., preferably 500-600° C.; and the calcination time is 5-8 hours.
8. A metal-loaded SBA molecular sieve prepared by the preparation method described in any one of claims 1 to 7.
9. The metal-loaded SBA molecular sieve according to claim 8, characterized in that: The surface of the metal-loaded SBA molecular sieve includes a silicon dioxide shell layer.
10. Use of the metal-loaded SBA molecular sieve according to claim 8 or 9 in CO methanation reaction.
11. The use according to claim 10, characterized in that: The reaction temperature is 180-230°C; And / or, the CO methanation reaction includes a reaction of a reaction mixture under the action of the metal-loaded SBA molecular sieve, and the reaction mixture includes H2, CO and N2; preferably, the volume ratio of H2, CO and N2 in the reaction mixture is 2 to 4:1:1.
Citation Information
Patent Citations
Load type metal mesoporous molecular sieve noble metal catalyst and preparation method thereof
CN104857983A
Preparation method and application of manganese-doped 4A molecular sieve
CN110201632A
Preparation method and application of core-shell type metal zeolite catalyst
CN112844456A
Method for obtaining metal oxides supported on mesoporous silica particles
CN113874318A
Catalyst particle and method for manufacturing aromatic derivative using the same
JP2003062466A